واقع تطبيق المديرين لمبادئ التخطيط الاستراتيجي للموارد البشرية في المؤسسات الاقتصادية الجزائرية (دراسة ميدانية لعينة من المؤسسات الصناعية الجزائرية) - مزاور, امال; بلعيد, ذهبية (جامعة الوادي - University of Eloued, 2022)
يتمثل غرضنا الدراسي في التعرف على واقع تطبيق المديرين لمبادئ التخطيط الاستراتيجي للموار د البشرية في المؤسسات الصناعية الجزائرية، أي مدى سهرهم على إدراك كل ما يتعلق بتخطيط الموارد البشرية للوصول الى مدى ادراكهم لمفهوم التخطيط الاستراتيجي للموارد البشرية و مكانتها. و قد توصلنا في الأخير الى عدة نتائج و التي من أهمها انه لم يتمكن المديرين من التطبيق الفعال للتخطيط الاستراتيجي للموارد البشرية الا بصفة محدودة، و يتبين ذلك في فشلهم في احترام اهم المفاهيم المتعلقة بتخطيط الموارد البشرية Our academic purpose is to identify the practice of managers for the principle of strategic planning for humanity in Algerian industrial enterprises , however to see all of the basic concepts of human ressorces planning to reach the concept of strategic planning and its position. We have reached the latter to several results , most notably, managers have not been able to effectively for strategic human resources strategic planning , and this is indicative to their failure to respect the most important concepts on human resources planning .
The reality of manager’s application of the principles of strategic planning of human resources in Algerian economic institutions (A field study of a sample of Algerian industrial enterprises)
مقال
Keywords: التخطيط الاستراتيجي ; إدارة الموارد البشرية ; تنمية المهارات